2013
DOI: 10.1159/000354028
|View full text |Cite
|
Sign up to set email alerts
|

Altered T Helper 17 Responses in Children with Food Allergy

Abstract: Background: While a central role for the T helper (Th) 1/Th2 axis in food allergy has been established, the Th17 response in food-allergic humans has not been addressed. Methods: Th17 responses in 18 peanut-allergic children, who were also allergic to at least one additional food allergen, were assessed relative to 15 age-matched healthy controls. To account for the atopy background in the allergic children, 7 atopic, but not food-allergic, individuals and their age-matched controls were included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Furthermore, these results are consistent with the higher level of Th2 cytokines, IL-4 and IL-6, and unaltered or lower levels of the Th1 cytokine, IFN-γ, in the intestinal mucosa of patients and mice with food allergy [11,38,50,51] . In light of our previous observation of IL-17 in this animal model and the significance of altered Th17 responses in food allergy [19,52] , future studies should be directed toward examining the contribution and interplay of Th1/Th2 as well as Th17 response in food allergies. Finally, because subjects who have outgrown their peanut allergy and those who are under potential treatment for allergies both exhibit a shifted Th1/Th2 cytokine profile, clearly further studies on cytokine profiles should be pursued [53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, these results are consistent with the higher level of Th2 cytokines, IL-4 and IL-6, and unaltered or lower levels of the Th1 cytokine, IFN-γ, in the intestinal mucosa of patients and mice with food allergy [11,38,50,51] . In light of our previous observation of IL-17 in this animal model and the significance of altered Th17 responses in food allergy [19,52] , future studies should be directed toward examining the contribution and interplay of Th1/Th2 as well as Th17 response in food allergies. Finally, because subjects who have outgrown their peanut allergy and those who are under potential treatment for allergies both exhibit a shifted Th1/Th2 cytokine profile, clearly further studies on cytokine profiles should be pursued [53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 94%
“…Thus, while we did not note increased levels of IL-17, IL-13, and IL-4 in ASD participants with food allergies compared to TD participants, we did observe that TD participants with food allergies produced higher levels of IL-17 compared to TD controls and ASD participants without food allergies. In a recent study of typically developing children with reported food allergies, the investigators found a higher production of IL-13 and IL-4 from in vitro isolated PBMC following a stimulation with a native peanut allergy mixture (Dhuban et al, 2013). While the T cell stimulation was directed towards a specific allergen rather than a pan-T cell mitogen, the cytokine profile was similar to what was noted in the current study for the typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, Dhuban et al [34] found significantly lower IL-17 production by Th17 T cells derived from the peripheral blood of food-allergic individuals when compared to PBMCs of healthy controls. For that purpose, PBMCs were cultured with peanut allergen Ara h 1 or 2, gliadin or tetanus toxoid for 9 days.…”
Section: Th17 Cellsmentioning
confidence: 89%